2013
DOI: 10.17269/cjph.104.4027
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Front-of-package Labelling Systems and Healthiness of Foods

Abstract: OBJECTIVE:The purpose of this study was to assess the impact of four different front-of-package (FOP) labelling systems on consumer perception and purchasing intent of food, and whether these systems help consumers select a balanced pattern of eating. METHODS:The four FOP labelling systems studied included two nutrient-specific systems -the Traffic Light (TL) and the Guideline Daily Amount (GDA) -and two summary indicator systems -NuVal ® and My-5 ® . Phase 1 was a small study with 36 participants to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
1
28
0
1
Order By: Relevance
“…The traffic light and 'high in' warning INRS also ranked significantly higher for providing nutritional information that participants can use and for understanding the nutrient levels in comparison to that of the star rating app but did not differ with the ranking of the control (NFt). These findings are similar to those of previous research conducted in USA, UK, or Chile, where consumers indicated higher preference for nutrient specific systems, such as traffic light labels or 'high in' warning labels in comparison to a summary INRS system or control [52,[62][63][64][65][66][67][68][69][70]. For example, a web-based survey simulating an online grocery store, administered to 1182 people in Chile, indicated improved participants' ability to perform a healthful food purchase when randomized to FOP nutrition information (modified traffic light system or the Chilean warning system) in comparison to the control condition [52].…”
Section: Discussionsupporting
confidence: 89%
“…The traffic light and 'high in' warning INRS also ranked significantly higher for providing nutritional information that participants can use and for understanding the nutrient levels in comparison to that of the star rating app but did not differ with the ranking of the control (NFt). These findings are similar to those of previous research conducted in USA, UK, or Chile, where consumers indicated higher preference for nutrient specific systems, such as traffic light labels or 'high in' warning labels in comparison to a summary INRS system or control [52,[62][63][64][65][66][67][68][69][70]. For example, a web-based survey simulating an online grocery store, administered to 1182 people in Chile, indicated improved participants' ability to perform a healthful food purchase when randomized to FOP nutrition information (modified traffic light system or the Chilean warning system) in comparison to the control condition [52].…”
Section: Discussionsupporting
confidence: 89%
“…These studies have focused on assessing consumers' ability to correctly interpret the information being presented (e.g. Maubach, Hoek and Mather 2014;van Herpen, Hieke and van Trijp 2014;Watson et al 2014) and their self-reported behavioural intentions (Aschemann-Witzel et al 2013;Newman, Howlett and Burton 2014;Savoie et al 2013;van Herpen and van Trijp 2011). Analysis is also complicated by difficulties associated with combining familiar and unfamiliar FoPLs, which makes it difficult to account for the effects of novelty and inexperience when interpreting results.…”
Section: Introductionmentioning
confidence: 99%
“…However, many such systems are proprietary, confidential, and not in the public domain. Their impact on improving diet quality remains to be seen (33,34). In the European Union, nutrient profiling was initially developed to qualify (or disqualify) foods from making a health or a nutrition claim.…”
Section: Current Status Of Knowledgementioning
confidence: 99%